Segmental resection of myxoid chondrosarcoma: a case report - Liu, Qinghao; Wu, Xing; Zhao, Weiwen; Peng, Junjie; Yin, Hao (Frontiers in Oncology, 2025)
We report a rare case of extradural spinal chondrosarcoma in a 48-year-old female. The patient was asymptomatic until a traumatic injury led to lumbar pain, revealing a tumor with atypical imaging characteristics in adjacent vertebral segments. MRI confirmed an extradural spinal tumor, which was surgically excised. Histopathological examination identified the tumor as myxoid chondrosarcoma. The patient underwent extensive surgical treatment, with no local recurrence or distant metastasis observed after five years. Her lumbar pain also completely resolved within the first postoperative year. The management of the rare entity of spinal canal chondrosarcoma is discussed.